2020
DOI: 10.2514/1.g004643
|View full text |Cite
|
Sign up to set email alerts
|

Power-Optimal Guidance for Planar Space Solar Power Satellites

Abstract: This paper presents power-optimal guidance for a planar space solar power satellite (SSPS).Power-optimal guidance is the attitude trajectory that maximizes the solar power transmitted by the SSPS. Maximizing the transmitted power simultaneously maximizes the cumulative energy delivered to the receiving station. Planarity couples the orientations of the SSPS's photovoltaic and antennas surfaces. Hence, the transmitted power only depends on the relative geometry between the SSPS, Sun, and receiving station. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 21 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…We remark that Problem 1 intentionally neglects both orbital maneuvering costs (for formation maintenance and stationkeeping) and attitude maneuvering costs (for slewing and rejecting disturbance torques/desaturating momentum devices). Preliminary studies for space vehicles with modern electric propulsion thrusters for orbit and attitude control have shown that the propellant masses required for orbital [33] and attitude [37] maneuvering in the absence of external perturbations are likely a negligible fraction of the total space vehicle mass over a 10-15 year lifetime. In contrast, the power transmission efficiency (by way of the geometric efficiency) is a significant contributor to the system's LCOE.…”
Section: Power-optimal Guidance Problem For a Constellationmentioning
confidence: 99%
“…We remark that Problem 1 intentionally neglects both orbital maneuvering costs (for formation maintenance and stationkeeping) and attitude maneuvering costs (for slewing and rejecting disturbance torques/desaturating momentum devices). Preliminary studies for space vehicles with modern electric propulsion thrusters for orbit and attitude control have shown that the propellant masses required for orbital [33] and attitude [37] maneuvering in the absence of external perturbations are likely a negligible fraction of the total space vehicle mass over a 10-15 year lifetime. In contrast, the power transmission efficiency (by way of the geometric efficiency) is a significant contributor to the system's LCOE.…”
Section: Power-optimal Guidance Problem For a Constellationmentioning
confidence: 99%